Quadratic stochastic Sarymsakov operators - Saburov, Mansoor (Institute of Physics Publishing, 2016)
In this paper, we introduce a new class of quadratic stochastic operators so-called Sarymsakov operators. We study the dynamics of such kind of operators. We establish regularity of each operator from this class. Note that there are some quadratic stochastic Sarymsakov operators which are not contraction mappings.